2001
DOI: 10.1073/pnas.141219498
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear particles containing RNA polymerase III complexes associated with the junctional plaque protein plakophilin 2

Abstract: Plakophilin 2, a member of the arm-repeat protein family, is a dual location protein that occurs both in the cytoplasmic plaques of desmosomes as an architectural component and in an extractable form in the nucleoplasm. Here we report the existence of two nuclear particles containing plakophilin 2 and the largest subunit of RNA polymerase (pol) III (RPC155), both of which colocalize and are coimmunoselected with other pol III subunits and with the transcription factor TFIIIB. We also show that plakophilin 2 is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
101
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 45 publications
0
101
0
Order By: Relevance
“…The plakophilins, which are armadillo-related proteins, contain ten 42-amino acid armadillorepeat motifs and are located in the outer dense plaque of desmosomes linking desmosomal cadherins with desmoplakin and the intermediate filament system 8 . Like other armadillo-repeat proteins, plakophilins are also found in the nucleus, where they may have a role in transcriptional regulation 9 . Plakophilin-2 exists in two alternatively spliced isoforms (2a and 2b), interacts with multiple other cell adhesion proteins and is the primary cardiac plakophilin 8,10 .…”
mentioning
confidence: 99%
“…The plakophilins, which are armadillo-related proteins, contain ten 42-amino acid armadillorepeat motifs and are located in the outer dense plaque of desmosomes linking desmosomal cadherins with desmoplakin and the intermediate filament system 8 . Like other armadillo-repeat proteins, plakophilins are also found in the nucleus, where they may have a role in transcriptional regulation 9 . Plakophilin-2 exists in two alternatively spliced isoforms (2a and 2b), interacts with multiple other cell adhesion proteins and is the primary cardiac plakophilin 8,10 .…”
mentioning
confidence: 99%
“…Note that most of the symplekin is recovered in particles with a peak value of ϳ11S, whereas minor portions appear with a mean peak corresponding to ϳ65S or in the pellet. Interestingly, all so far characterized nuclear forms of junctional plaque proteins have in common that they are somehow involved in processes of transcription, splicing, or 3Ј-end processing: Plakophilin 2 has been detected in RNA polymerase III complexes, p120 ctn and ␤-catenin are involved in regulations of RNA polymerase II transcription, and protein 4.1 has been found in splicing factors (Behrens et al, 1996;Huber et al, 1996;Molenaar et al, 1996;Krauss et al, 1997;Lallena et al, 1998;Daniel and Reynolds, 1999;Mertens et al, 2001). Symplekin is the first protein associated with factors involved in 3Ј-end processing of premRNA in the nucleus as well as in cytoplasmic translational control.…”
Section: Molecular Biology Of the Cell 1672mentioning
confidence: 99%
“…To elucidate the nuclear function(s) of symplekin we have applied biochemical methods for isolating and characterizing the protein, using methods that recently have been successful in studies of the nuclear forms of plakophilin PKP2, which has been shown to be part of RNA polymerase III complexes (Mertens et al, 2001). For the sake of clarity we have further decided to start with the exceptionally large nuclei of Xenopus laevis oocytes ("germinal vesicles") allowing both mass and manual isolations with minimal cytoplasmic contamination as well as the preparation of enucleated "ooplasms," and thus the parallel analysis of both karyoplasm and cytoplasm (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Nuclear plakophilin-2 localization has been previously reported; however, the functional role of plakophilin-2 in the nucleus is currently unknown (Mertens et al 1996). Previous reports have identified RNA polymerase III as a nuclear binding partner of plakophilin-2 (Mertens et al 2001); however, the functional consequences of this interaction have not been investigated. Attempts to identify additional nuclear binding partners in A431 cells were unsuccessful.…”
mentioning
confidence: 97%